IMMU-13. MECHANISMS OF IMMUNOLOGICAL ESCAPE DURING ADOPTIVE CELLULAR THERAPY IN HIGH GRADE GLIOMA. (11th November 2019) - Wildes, Tyler; Dyson, Kyle; Francis, Connor; Wummer, Brandon; Yang, Changlin; Yegorov, Oleg; Shin, David; Grippin, Adam; Divita, Bayli; Mitchell, Duane; Flores, Catherine
Abstract: INTRODUCTION: Immunotherapy is remarkably effective, yet tumor escape is common. Herein, we investigated tumor escape after adoptive cellular therapy (ACT) in intractable glioma models. These studies revealed multiple mechanisms of escape including a shift in immunogenic tumor antigens, downregulation of MHC-I, and upregulation of checkpoint molecules. Despite these changes, we HYPOTHESIZED that a new population of escape variant-specific polyclonal T cells could be generated to target immune-escaped tumors through using tumor escape variant RNA. METHODS: We studied KR158B-luc glioma-bearing mice during treatment with ACT with polyclonal tumor-specific T cells. We tested the immunogenicity of primary and escaped tumors using T cell restimulation assays. We used flow cytometry and RNA profiling of whole tumors to further define escape mechanisms. To treat immune-escaped tumors, we generated escape variant-specific T cells through the use of escape variant total tumor RNA and administered these cells as ACT. RESULTS: Escape mechanisms included a shift in immunogenic tumor antigens, downregulation of major histocompatibility complex (MHC) class I by 50%, and upregulation of checkpoint molecules. This included activated T cells and NK cells from tumor-draining lymph nodes expressing 50% and 30% PD-1 after ACT. Importantly, polyclonal T cells specific for escape variants displayed greater recognition of escaped tumors than primary tumors. When administered as ACT, these T cells prolonged median survival of escape variant-bearing mice by 60% (24 to 33 days, p=.0003). The rational combination of ACT with PD-1 blockade prolonged median survival of escape variant glioma-bearing mice by 110% and was dependent upon NK cells and T cells as determined by cell depletion experiments. To prevent escape from primary tumors, we combined ACT with PD-1 blockade to yield 71% long-term cures in KR158B-luc-bearing mice. CONCLUSIONS: These findings suggest that the immune landscape of brain tumors is markedly different post-immunotherapy yet can still be targeted with immunotherapy.